2020
DOI: 10.1002/jwmg.21931
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Prey Selection of Dholes in Evergreen and Deciduous Forests of Southeast Asia

Abstract: Endangered dholes (Cuon alpinus) are restricted to small and declining populations in Southeast Asia, and little is known about how their ecology differs within the region. We used DNA‐confirmed scats and prey surveys to determine the seasonal diet and prey selection of dholes in 2 different landscapes that dominate Southeast Asia: closed evergreen forests in hilly terrain in northern Laos, and open deciduous forests in relatively flat terrain in eastern Cambodia. On both sites, muntjac (Muntiacus spp.; 20–28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…It also overlapped with Asiatic black bear in the high level (Δ =0.76). Asiatic black bear was also found in the list of dhole food (Kamler et al 2020).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It also overlapped with Asiatic black bear in the high level (Δ =0.76). Asiatic black bear was also found in the list of dhole food (Kamler et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The species of wild animals with significant spatialtemporal overlap with dhole, tiger, and leopard, as well as dhole prey species from the study of Charaspet et al (2020); Khoewsree et al (2020), and Kamler et al (2020); prey species of tiger from the study of Phetdee (2000), and prey species of leopard from the study of Simcharoen (2008) were studied to understand the potential wild animal prey of the large carnivores. It was found that there were 11 species of wild animals with significant spatial overlap with dhole, tiger, and leopard.…”
Section: The Spatial-temporal Overlap Of Dhole Tiger Leopard and Other Wild Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the wet season when the NDVI increased, Sambar and Northern Red Muntjac began to be detected more often than Gaur and Asian Elephant. Northern Red Muntjac and Sambar were the main prey of Dhole (Intaraprasit et al, 2017;Kamler et al, 2020), so Dhole should be one of the carnivores that is specific to the forest edge, especially during the wet season. One point of concern is that Dhole may potentially catch certain diseases from domestic dogs at the forest edge, since Dhole is susceptible to Canine Distemper (Sillero-Zubiri et al, 2004), a lethal disease among domestic dogs which is prevalent in the villages.…”
Section: Resultsmentioning
confidence: 99%